2017
DOI: 10.1021/acs.jpcb.7b07780
|View full text |Cite
|
Sign up to set email alerts
|

Proton Diffusion through Bilayer Pores

Abstract: The transport of protons through channels in complex environments is important in biology and materials science. In this work, we use multistate empirical valence bond simulations to study proton transport within a well-defined bilayer pore in a lamellar L phase lyotropic liquid crystal (LLC). The LLC is formed from the self-assembly of dicarboxylate gemini surfactants in water, and a bilayer-spanning pore of radius of approximately 3-5 Å results from the uneven partitioning of surfactants between the two leaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 124 publications
1
4
0
Order By: Relevance
“…The motif that hydronium ions nucleate their own water clusters/transport networks is similar to that observed in studies of other systems: for example, Peng et al . have shown that an excess proton can create its own water wires in confined environments such as carbon nanotubes and other hydrophobic cavities. ,, We note that previous work on proton transport in surfactant-based lyotropic liquid crystals emphasized the importance of interactions of the hydronium oxygen atom with hydrophobic moieties on the surfactants. , We have computed correlation functions between the oxygen atom of the hydronium ion and aliphatic chains of the BMIM + cation, which are shown in Figure S14; while there is a tendency for coordination with the hydrophobic BMIM + tail, concentration effects are subtle and appear relatively minor.…”
Section: Resultssupporting
confidence: 75%
See 4 more Smart Citations
“…The motif that hydronium ions nucleate their own water clusters/transport networks is similar to that observed in studies of other systems: for example, Peng et al . have shown that an excess proton can create its own water wires in confined environments such as carbon nanotubes and other hydrophobic cavities. ,, We note that previous work on proton transport in surfactant-based lyotropic liquid crystals emphasized the importance of interactions of the hydronium oxygen atom with hydrophobic moieties on the surfactants. , We have computed correlation functions between the oxygen atom of the hydronium ion and aliphatic chains of the BMIM + cation, which are shown in Figure S14; while there is a tendency for coordination with the hydrophobic BMIM + tail, concentration effects are subtle and appear relatively minor.…”
Section: Resultssupporting
confidence: 75%
“…Additionally, a different choice of anion may favor the Zundel configuration instead of the Eigen configuration, with benefits for proton transport rates. The many previous examples of enhanced proton transport in low-water-content systems ,,, suggest much room for further optimization of ionic liquid based proton conducting solutions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations